Does quantity make the difference? Associations between the amount of physical education and children's basic motor competencies - Marina Wälti; Lucas Schole; Uwe Pühse; Erin Gerlach; Jeffrey Sallen; Claude Scheuer; Christian Herrmann (Bern Open Publishing, 2023)
Basic motor competencies (BMC) belong to the main learning goals of physical education (PE) in primary school and are needed to actively take part in the culture of sport and human movement. BMC levels between European countries differ widely and individual determinants like age, sex, and extracurricular physical activity participation consistently predict BMC levels (Wälti et al., 2022), but also structural aspects of PE are important factors of learning outcomes. In this study, we wanted to investigate if the weekly amount of PE accounts for differences in BMC levels across countries. We assessed BMC (object movement, self-movement), anthropometric data (sex, age, body-mass-index) and participation in extracurricular physical activity (ball sports, individual sports) in 3,069 6- to 10-year-old primary school children using the MOBAK-1-4 and structural aspects (amount of PE) in 179 teachers from eight European countries. Latent multilevel regression analyses were corrected for children's sex, age, body-mass-index, extracurricular physical activity participation and region of assessment. Despite differences in the weekly amount of PE in the assessed samples, there were no significant associations between the amount of PE and object movement or self-movement in either the 6- to 8-year-old or the 8- to 10-year-old children. The covariates age, sex, body-mass-index and participation in ball sports were significant predictors of object movement in all children. Body-mass-index and participation in any kind of extracurricular physical activity were significantly associated with self-movement in children aged 6-8 years. In children aged 8-10 years, all anthropometric variables as well as participation in any kind of extracurricular physical activity were significant predictors of self-movement. Other country-specific or PE-related factors might be more crucial for the differences in BMC levels than the amount of PE (García-Hermoso et al., 2020). A focus on the quality and content of PE lessons as well as on the qualification and goals of PE teachers is suggested. Nevertheless, for children who do not participate in extracurricular physical activity, PE can be crucial for BMC development. References García-Hermoso, A., Alonso-Martínez, A. M., Ramírez-Vélez, R., Pérez-Sousa, M. Á., Ramírez-Campillo, R., & Izquierdo, M. (2020). Association of physical education with improvement of health-related physical fitness outcomes and fundamental motor skills among youths: A systematic review and meta-analysis. JAMA Pediatrics, 174(6), Article e200223. https://doi.org/10.1001/jamapediatrics.2020.0223 Wälti, M., Sallen, J., Adamakis, M., Ennigkeit, F., Gerlach, E., Heim, C., Jidovtseff, B., Kossyva, I., Labudová, J., Masaryková, D., Mombarg, R., De Sousa Morgado, L., Niederkofler, B., Niehues, M., Onofre, M., Pühse, U., Quitério, A., Scheuer, C., Seelig, H., Vlček, P., . . . & Herrmann, C. (2022). Basic motor competencies of 6- to 8-year-old primary school children in ten European countries: A cross-sectional study on associations with age, sex, BMI and physical activity. Frontiers in Psychology, 13, Article 804753. https://doi.org/10.3389/fpsyg.2022.804753